Advances in Artificial and Biological Membranes: Mechanisms of Ionic Sensitivity, Ion-Sensor Designs and Applications for Ions Measurement - Lewenstam, Andrzej; Dołowy, Krzysztof (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Ion-sensitive membrane-based sensors and ionic processes in bio-membranes are the focus of this book. The chapters are carefully chosen to characterize essential research trends, applications, and perspectives. They include solid contact ion-selective and reference electrodes and their electroanalytical behavior in zero and nonzero-current modes, planar and miniaturized multielectrode platforms, ion monitoring in extreme sports, and transmembrane transport through living endothelial cells to find the volume. This book is crowned by the consideration of a yet unexplored ion status in a mitochondrial matrix